Flagship 3: Inclusive and efficient value chains - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2018)
Making food markets work for the poor ● Evaluating the impact of trade policies on value chains, income, and food security ● Measuring and reducing food losses ● Interventions to improve the efficiency of agricultural value chains ● Innovations in crop insurance that work for poor farmers ● Lessons in scaling up interventions